Overview of lupus nephritis management guidelines and perspective from Asia. Issue 1 (January 2014) - Mok, Chi Chiu; Yap, Desmond YH; Navarra, Sandra V; Liu, Zhi‐hong; Zhao, Ming‐hui; Lu, Liangjing; Takeuchi, Tsutomu; Avihingsanon, Yingyos; Yu, Xue‐qing; Lapid, Elizabeth A; Lugue‐Lizardo, Lenrore R; Sumethkul, Vasant; et al.
Abstract Lupus nephritis (LN) is a common and important manifestation of systemic lupus erythematosus (SLE). Evidence suggests higher rates of lupus renal involvement in Asian populations, and maybe more severe nephritis, compared with other racial or ethnic groups. The management of LN has evolved considerably over the past three decades, based on observations from clinical studies that investigated different immunosuppressive agents including corticosteroids, cyclophosphamide, azathioprine, mycophenolic acid, calcineurin inhibitors and novel biologic therapies. This is accompanied by improvements in both the short‐term treatment response rate and long‐term renal function preservation. Treatment guidelines for LN have recently been issued by rheumatology and nephrology communities in U.S.A. and Europe. In view of the racial difference in disease manifestation and response to therapy, and the substantial disease burden in Asia, a panel of 15 nephrologists and rheumatologists from different Asian regions with extensive experience in lupus nephritis – the Steering Group for the Asian Lupus Nephritis Network (ALNN) – met and discussed the management of lupus nephritis in Asian patients. The group has also reviewed and deliberated on the recently published recommendations from other parts of the world. This manuscript summarizes the discussions by the group and presents consensus views on the clinical management and treatment of adult Asian patients with LN, taking into account both the available evidence and expert opinion in areas where evidence remains to be sought.